Klaim Simbolik dalam Relasi Sosial-Politik Indonesia–Malaysia - Dewii, Citra Septia; Sabatini, Minerva Laisa; Arsyada, Ruby; Nurlia, Elly (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The cultural disputes between Indonesia and Malaysia are no longer mere arguments over the origins of batik, reog, or rendang; they mirror a deeper struggle for symbols and meaning within Southeast Asia’s socio-political landscape. Beneath the rhetoric of kinship lies tension over who holds the right to define “heritage” and whose story is recognized by the world. This study explores the symbolic dimensions of these cultural conflicts through a qualitative, literature-based approach that examines media narratives, diplomatic practices, and international legal frameworks. The findings reveal that cultural claims function as political instruments to assert national identity, yet simultaneously open spaces for negotiation and solidarity. When law and diplomacy fall short, culture becomes a living arena where nations contest dignity, memory, and belonging. Within this context, the concept of Shared Culture Diplomacy offers a middle path, inviting both nations to celebrate, rather than contest, their intertwined heritage as a testament to a broader fraternity beyond state boundaries.